Makna Warna Tata Rias Wajah Pemain Kabuki pada Video Shibaraku - Ni Nyoman Sariyanti; Ni Wayan Meidariani; Wayan Nurita (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2023)
This articel aims to find out the meaning of the colors of kabuki performance art makeup on the antagonist, protagonist and Princess characters in the Shibaraku video. Analysis of meaning using Peirce's semiotic theory through the classification of the types of signs seen from the object, namely icons in the form of pictures of kabuki figures, indexes in the form of colors and types of makeup used by kabuki characters and symbols in the form of color relations with the characters of kabuki characters. This classification of marks has been used to define color in kabuki makeup. The data source used in this paper is the primary data source in the form of a kabuki performance video entitled Shibaraku downloaded from YouTube. The method used in this paper is a qualitative method. Based on the results of data analysis, it is known that the meaning and name of the character's makeup, the makeup of the protagonist's character, namely the kumadori sujiguma makeup with red color which has the meaning of goodness and justice. Meanwhile, the makeup for the antagonist character is the kumadori kugeare makeup in blue which means cold or cruel. Also, Princess character makeup is a standard makeup with a white base color which means purity of character, and light red on the eyes which means femininity and cheerfulness. Keywords: color; kabuki; makeup; meaning.